Comparative EIS study of the adsorption and electro-oxidation of thiourea and tetramethylthiourea on gold electrodes - Bolzán, Agustín Eduardo (2014)
A comparative study of the electrochemical behaviour of thiourea (TU) and tetramethylthiourea (TMTU) on gold in sulphuric acid was performed using a gold rotating disc electrode. The electrochemical impedance spectra are interpreted through an equivalent circuit involving the electrolyte resistance, a constant phase element for the capacity double layer, a charge transfer resistance and, depending on the electrode potential, a second parallel impedance element whose interpretation depends on the potential region considered. Thus, for both thioureas, the Nyquist plots for E < −0.6 V (vs. MSE) exhibit a single capacitive time constant related to the adsorption of the molecule on the electrode surface. As E increases, the Nyquist plots exhibit a new time constant assigned to the formation of a soluble complex species. This time constant appears in the potential region also related to the electro-oxidation of the thioureas to the corresponding formamidinium disulphide. This means that these processes are coupled and, therefore, only one time constant can be observed. An inductive loop at low frequencies is associated with the pitting of the gold electrode for E ≥ −0.20 V, in agreement with SEM micrographs. The value of the corresponding charge transfer resistance decreases markedly with the electrode potential, indicating the increase in the rate of the electrochemical processes. Electrodissolution of gold results more importantly in the presence of TMTU. At potential values associated with the formation of the anodic oxide layer on gold, a negative resistance is recorded, indicating the passivation of the electrode surface. Eventually, at E > 0.6 V, the electrode surface passivation disappears and the Nyquist plots exhibit two strongly overlapped capacitive constants assigned to the oxide film growth at the monolayer level and the second electro-oxidation process of thioureas, the latter resulting in the formation of carbon dioxide and sulphate ions according to FTIRRAS data.